POLITENESS STRATEGIES AND THEIR FUNCTIONS IN COMMUNICATION - Umurova Feruza Pirmamat qizi; Abduvassiyeva Jasmina (Bright Mind Publishing, 2025)
This study analyzes the strategies of the polite category in speech and their communicative functions. Tactfulness is a form of culturally specific social attitude that plays an important role in ensuring positive communication between speech participants. The study explores how politeness strategies are expressed through different speech styles such as attentiveness, sincerity, respect and their impact on communication effectiveness. It also examines the role of the category of courtesy in communication, social norms, conflict prevention and creation of a positive image in terms of communicative functions. The results of the study serve to better understand the communicative functions of courtesy strategies in different contexts.
Keywords: Politeness, speech strategies, communicative functions, communication, social culture, speech acts, conflict prevention, creating a positive image.